Learning Islamic Education with the Project Based Learning (PjBL) Method - Nurul Latifatul Inayati; Haning Tyas Pratiwi (Yayasan Letiges Konsultan Sosial, 2025)
This study aims to analyze Islamic Education learning with project-based learning methods and identify obstacles and solutions faced in learning. The research approach used is qualitative with a phenomenological type. Data were collected through interviews, non-participatory observation, and documentation. The data analysis technique in this study follows the steps of Data Reduction, Data Presentation, and Conclusion Drawing. The study results indicate that implementing Islamic Education learning with the project-based learning method is carried out in stages based on the principles of project-based learning, determining the main questions, project planning, making an implementation schedule, creating projects, and evaluating the results. This learning emphasizes students' active involvement in completing projects relevant to the learning material to create a pleasant learning atmosphere and increase motivation, creativity, and critical thinking skills. Some obstacles to implementing the project-based learning method are immature planning, time constraints, and difficulties in managing groups of students. To overcome these obstacles, cooperation is needed from all parties, both teachers, students, and schools. Teachers, as facilitators, can provide appropriate direction for students regarding project planning, condition learning effectively, and create a supportive learning environment.